2022
DOI: 10.1021/jacs.1c13213
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure of Lithium Dendrites Revealed by Room-Temperature Electron Microscopy

Abstract: The uncontrolled deposition/dissolution process of lithium dendrites during electrochemical cycling in batteries limits the large-scale application of Li metal anodes. Investigating the microstructure of Li dendrites is a focal point. Currently, the only way to protect and observe sensitive Li dendrites is through low-temperature transmission electron microscopy (LT-TEM), whereas room-temperature characterization is still lacking. In this work, the room-temperature microstructure of Li dendrites was obtained b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 44 publications
1
16
0
Order By: Relevance
“…Therefore, the cryogenic imaging still needs to be optimized to achieve better image quality. The situation here is similar to that which has been pointed out in our previous work on beam-sensitive lithium metals; a low temperature can better protect the structure from beam damage while side effects exist. In contrast, room-temperature imaging provides feasibility for multimodal characterizations while the dose/dose rate should be kept lower than that under the cryogenic condition.…”
supporting
confidence: 84%
“…Therefore, the cryogenic imaging still needs to be optimized to achieve better image quality. The situation here is similar to that which has been pointed out in our previous work on beam-sensitive lithium metals; a low temperature can better protect the structure from beam damage while side effects exist. In contrast, room-temperature imaging provides feasibility for multimodal characterizations while the dose/dose rate should be kept lower than that under the cryogenic condition.…”
supporting
confidence: 84%
“…With a controlled electron dose rate (0.89 e À Å À2 s À1 ), Li metal and SEI layers can be imaged at room temperature. 39 In this work, in situ TEM with a very low electron dose rate (0.33 e À Å À2 s À1 ) was used to probe the Li stripping/deposition process across the SEI layer to avoid electron beam damage to Li and SEI layers at room temperature. Therefore, the electron beam damage to Li and SEI layers has been well mitigated.…”
Section: Papermentioning
confidence: 99%
“…Previous studies have reported many different Li deposit morphologies: hemi-sphere, 3,4 granular, 5–7 columnar (or nanorod), 8,9 whisker (needle-like), 10,11 Eden cluster, 12 mossy (bush-like), 13 and dendrite (tree-like). 14,15 The morphology of the Li deposit governs the performance of the lithium metal anode.…”
Section: Introductionmentioning
confidence: 99%
“…To outperform a LIB in terms of energy density and cycle life (80% capacity retention at 1000th cycle), a LMB should have o3.5 Â excess of Li, 1 an anode coulombic efficiency (CE) of 499.83%, and an anode porosity of o65%. 2 Previous studies have reported many different Li deposit morphologies: hemi-sphere, 3,4 granular, [5][6][7] columnar (or nanorod), 8,9 whisker (needle-like), 10,11 Eden cluster, 12 mossy (bush-like), 13 and dendrite (tree-like). 14,15 The morphology of the Li deposit governs the performance of the lithium metal anode.…”
Section: Introductionmentioning
confidence: 99%